An Efficient Decentralized Identity Management System Based on Range Proof for Social Networks - Xinjie Zhu; Debiao He; Zijian Bao; Min Luo; Cong Peng (IEEE Open Journal of the Computer Society, 2023)
Online social networks (OSNs) are becoming more and more popular in people's lives as the demand for online interaction continues to grow. Current OSNs are using centralized identity management system (IDM), which has some problems of single point of failure and privacy data leakage. The emergence of decentralized identity (DID) can solve these problems. However, most existing DID systems have some privacy issues that a user's attributes value are disclosed while accessing service. In this paper, we design a DID protocol to solve these challenges. The proposed protocol includes a range proof protocol to provide attribute privacy. The range proof protocol works with anonymous credentials and does not need a trusted setup. Moreover, the identity model behind the DID protocol is extended from an existing model, which achieves identity revocation. Finally, we implement a system prototype on the blockchain for evaluation. The security analysis shows that our protocol provides stronger privacy protection. The performance evaluation indicates that the computation cost and blockchain overheads of our protocol are acceptable in OSNs.